A REPERCUSSÃO DA LEGISLAÇÃO NA DINÂMICA DO USO DA TERRA NA BACIA DO RIO CARÁ-CARÁ, PONTA GROSSA – PR, NO PERÍODO DE 1980 A 2007 - Freitas, Andreza Rocha de (2008)
The human ownership of area causes transformations. To what such transformations causes the least possible impact strategies are necessary to soften down changes anthropic, that can be accompanied and identified by means of land use, of delineation of areas of environmental conflicts and the identification of areas that suffered more changes in their natural characteristics. These studies do part of environmental planning, because offer information necessary to development of strategies and shares to ease the impacts caused at anthropic interference. To do so is necessary to establish environmental units from their morphological features that feasibly area of search, as, for example, the hydrographic basin, which are a natural system delimited in space. The hydrographic basin in study is the Cará-Cará River, located in the southeastern municipal district of Ponta Grossa - PR. The general objective of this work was examine the dynamics of occupation of the land use in aforesaid basin, between the years 1980 and 2007, and the repercussion of laws in force in the land use. To that end, it was necessary to search and draw up maps of relevant legislation, of slope and land use that, through SPRING 4.3.3, were overlay until they reach to maps synthesis of conflicts land use. To facilitate the identification of areas that most suffered the influence anthropic were elaborated letters of hemeroby. It was found that the category of land use that more increased in the period studied was the urbanized (121.83%) and the category reforestation decreased by 30.69%. As for conflicts environmental land use, 21.05% of the area of the basin is in conflict (areas over-used and underused). Through the maps of hemeroby, it was found that the areas ahemeorobe (landscapes with little or no human interference) decreased by 24.51% and category oligohemeorobe (landscapes more natural than artificial) is the predominant in the basin with 41.94%. It was concluded that the changes in the basin Cará-Cará River were motivated by guidelines established in the Plans Directors of Ponta Grossa of 1967, 1992 and 2006. This work is an allowance for future studies, planning and projects to be undertaken by the public agency responsible.